(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Academic writing in English poses numerous challenges for non-native speakers, significantly affecting their academic success and participation in scholarly discourse. The foundation of scholarly communication is academic writing, which allows researchers to communicate their discoveries, make arguments, and increase our understanding. However, generating excellent academic writing in English poses special difficulties for non-native English speakers (NNES). These difficulties are caused by cultural norms, rhetorical devices, educational backgrounds, and linguistic disparities. The pressure on NNES researchers to publish in English has increased as English has emerged as the dominant language of academia, especially in the social and scientific sciences. This article examines the various problems that non-native English speakers encounter when writing academically and suggests solutions.